Pouch surgery for ulcerative colitis in 2025: A narrative review - Vignali, Andrea; Sileri, Pierpaolo (Baillière's best practice & research. Clinical gastroenterology, 2025)
Restorative proctocolectomy with ileoanal pouch is the standard procedure in ulcerative colitis patients with medical refractory disease, dysplasia or in selected patients with Crohn's disease. The advent of biologics has reduced the rate of elective colectomies, the timing of surgery and the type of the surgical approach and increased the stages of the operation. to analyze the main chances in pouch surgery with a focus on staging, minimally invasive surgery and trans anal approach. the decision on the staging approach should be individualized according to disease severity, preoperative nutritional status, intraoperative variables and preoperative exposure to immunomodulators. A minimally invasive approach is recommended when feasible. Trans-anal ileal pouch is a promising technically demanding operation, subject to procedure specific risk and should be performed only by experienced surgeons. The minimally invasive approaches are evolving, but large-scale controlled studies are needed to confirm their efficacy and safety.